The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1158/1078-0432.ccr-21-1643
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Landscape of Early-Stage Ovarian High-Grade Serous Carcinoma

Abstract: Purpose: Ovarian high-grade serous carcinoma (HGSC) is usually diagnosed at late stage. We investigated whether late-stage HGSC has unique genomic characteristics consistent with acquisition of evolutionary advantage compared with early-stage tumors. Experimental Design: We performed targeted next-generation sequencing and shallow whole-genome sequencing (sWGS) on pretreatment samples from 43 patients with FIGO stage I–IIA HG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 45 publications
5
47
1
Order By: Relevance
“…CN signature 4, marked by high segment copy number, was significantly associated with whole genome duplication and mutations in the PI3K/AKT pathway (37). Our recent comparison of early-and late-stage HGSC genomes confirmed the link between CN signature 4 and high ploidy, as well as its association with poor prognosis (38). Here, we showed that high CN signature 4 exposure was again negatively prognostic in the control arm but was associated with an improvement in PFS in the experimental arm, although this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 61%
“…CN signature 4, marked by high segment copy number, was significantly associated with whole genome duplication and mutations in the PI3K/AKT pathway (37). Our recent comparison of early-and late-stage HGSC genomes confirmed the link between CN signature 4 and high ploidy, as well as its association with poor prognosis (38). Here, we showed that high CN signature 4 exposure was again negatively prognostic in the control arm but was associated with an improvement in PFS in the experimental arm, although this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 61%
“…Cheng and colleagues ( 1 ) reported similar age-at-diagnosis comparing early- and late-stage HGSC as evidence to support their distinct developmental origins. While this observation is intriguing, it would be of interest to further investigate whether early-stage disease was related to the patient's primary differential diagnosis or was discovered incidentally.…”
mentioning
confidence: 92%
“…In this issue of Clinical Cancer Research , Cheng and colleagues ( 1 ) describe results from a retrospective, hypothesis-generating study that explores the evolutionary origins of high-grade serous ovarian cancer (HGSC) by comparing genomic differences of early-stage (stage IA–IIA; n = 46) to late-stage HGSCs (stage IIIC–IV; n = 52). As significant prognostic disparity exists between early- and late-stage HGSC, it is unclear whether early-stage disease represents a molecularly distinct subtype that lacks peritoneal dissemination potential or if it reflects a premetastatic precursor state of late-stage HGSC.…”
mentioning
confidence: 99%
See 2 more Smart Citations